Experimental evaluation of an ORC-CHP architecture based on regenerative preheating for geothermal applications. (1st June 2022) - Eyerer, Sebastian; Dawo, Fabian; Schifflechner, Christopher; Niederdränk, Anne; Spliethoff, Hartmut; Wieland, Christoph
Graphical abstract: Highlights: Regenerative preheating leads to up to 9.9% higher net thermal efficiency. Novel ORC-CHP architecture features large operation range and high part load efficiency. The net electricity production can be increased by up to 9.4% at equal heat output. An additional revenue of 4.56 million € can be generated during 20 years of operation. Abstract: The Organic Rankine Cycle (ORC) can be applied to generate power from low-temperature heat sources and thus supports a sustainable energy system. This paper contributes to ORC development, particularly for geothermal applications, to increase competitiveness of the technology. To this end, new plant architectures based on regenerative preheating are being investigated. The concept of regenerative preheating is investigated in literature by numerical studies and its thermodynamic and economic performance is predominantly evaluated positively. However, regenerative preheating has not yet been realized in experimental ORC test rigs or commercial products. For this purpose, a novel ORC test rig is designed, constructed and commissioned. For evaluation purposes, the regenerative preheating concept is compared to a standard ORC configuration. As a result, a 9.9% higher net thermal efficiency is achieved with regenerative preheating, while the net power output is equal to the one achieved with the standard configuration. This result is particularly important for combined heat and power (CHP) generation due to the reduced cooling of the heat source. In order to evaluate this concept for CHP applications, a novel ORC-CHP architecture based on regenerative preheating is experimentally compared to three state-of-the-art ORC-CHP concepts. Moreover, three different supply and return temperatures of the district heating system (DHS) are considered. The results reveal that the novel architecture, in combination with low- and medium-temperature DHS, leads to an increased part-load performance and a wider operating range. This enables up to 9.4% increase in annual net electricity production, which accounts for additional revenues of 4.56 million € in the case of a typical geothermal project. Thus, it can be concluded that this novel ORC-CHP architecture is beneficial from a technical perspective and also promising in terms of economics.